Development of a 4D dosimetry simulation system in radiotherapy. (29th March 2012) - Wu, Q. Jackie; Thongphiew, Danthai; Wang, Zhiheng; Willett, Christopher; Marks, Lawrence; Yin, Fang-Fang
4D CT image sets are used to encode patient-organ motion and to calculate the dose delivered during each respiratory phase. The dose-per-phase is summarised to the total dose via deformable registration. The system incorporates the actual beam parameters and synchronises the beam motion (e.g., gantry/MLC motion of the DARC and MLC motion of the IMRT) to the patient's respiratory motion. Furthermore, this system incorporates different treatment techniques such as 3D conformal (3DCRT), dynamic arc (DARC), and Intensity-Modulated Radiation Therapy (IMRT), thus allows better understanding of organ motion effect on dose delivery, treatment techniques and corresponding optimal margins.